2015
DOI: 10.1095/biolreprod.115.127969
|View full text |Cite
|
Sign up to set email alerts
|

Oviduct-Embryo Interactions in Cattle: Two-Way Traffic or a One-Way Street?1

Abstract: This study examined the effect of the presence of single or multiple embryos on the transcriptome of the bovine oviduct. In experiment 1, cyclic (nonbred, n = 6) and pregnant (artificially inseminated, n = 11) heifers were slaughtered on Day 3 after estrus, and the ampulla and isthmic regions of the oviduct ipsilateral to the corpus luteum were separately flushed. Oviductal epithelial cells from the isthmus region, in which all oocytes/embryos were located, were snap-frozen for microarray analysis. In experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 58 publications
2
99
4
Order By: Relevance
“…Thus, in pigs Almiñana et al (2012) showed that embryo-maternal communication exists at earliest stages of pregnancy, before the well-known embryonic signal of maternal recognition. In contrast, Maillo et al (2015) did not find differences in the bovine oviduct transcriptome in the presence or absence of an 8-to 16-cell embryo in vivo. Obviously, multi-ovulatory species like mice and pigs cannot be directly compared with mono-ovulatory species such as cattle.…”
Section: Embryo-maternal Communication In the Oviductcontrasting
confidence: 58%
See 1 more Smart Citation
“…Thus, in pigs Almiñana et al (2012) showed that embryo-maternal communication exists at earliest stages of pregnancy, before the well-known embryonic signal of maternal recognition. In contrast, Maillo et al (2015) did not find differences in the bovine oviduct transcriptome in the presence or absence of an 8-to 16-cell embryo in vivo. Obviously, multi-ovulatory species like mice and pigs cannot be directly compared with mono-ovulatory species such as cattle.…”
Section: Embryo-maternal Communication In the Oviductcontrasting
confidence: 58%
“…In a recent study from our group, it was necessary to transfer multiple embryos (up to 50) into the oviducts of heifers to detect differences in the transcriptome. When a single embryo was transferd into the oviduct (pregnant vs cyclic heifers) no differences were found, suggesting a local effect of the embryo (Maillo et al, 2015). More recently, Smits et al (2016) reported a local influence of the embryo on the transcriptome of the equine oviduct epithelium.…”
Section: Embryo-maternal Communication In the Oviductmentioning
confidence: 99%
“…In order to test the effect of region (ampulla vs isthmus), localization relative to the CL (ipsilateral vs contralateral), presence of sperm and presence of an embryo, the following array comparisons were carried out: (Maillo et al 2015); therefore it will not be discussed in this study.…”
Section: Changes In Oviduct Gene Expressionmentioning
confidence: 99%
“…We have previously described changes in the oviductal transcriptome in pregnant heifers following the transfer of multiple embryos (Maillo et al 2015). There is a paucity of data on the spatial variation on gene expression within the oviduct.…”
Section: Introductionmentioning
confidence: 99%
“…Today, the active role of the oviduct is becoming more and more clear with a growing list of activities both as preparation for an embryo to arrive as well as reactions to its actual presence (Artemenko et al, 2015;GonellaDiaza et al, 2015GonellaDiaza et al, , 2017Maillo et al, 2016b). One challenge for this kind of work seems to be able to detect the changes when they are only caused by a single embryo (Maillo et al, 2015).…”
Section: Maternal-embryonic Communicationmentioning
confidence: 99%